IMPLICATIONS OF NO VIRAL NO JUSTICE ON THE PRINCIPLE OF EQUALITY BEFORE THE LAW IN THE CRIMINAL JUSTICE SYSTEM - Eva Naura; Benny Sumardiana (Law Research Review Quarterly, 2026)
This study aims to examine the phenomenon of No Viral No Justice in law enforcement practices in Indonesia in the digital era, as well as identify the positive and negative impacts of the role of social media as a means of social control on law enforcement officials. The main problem in this study stems from the dependence of law enforcement officials on the pressure of public opinion, raising serious problems related to objectivity, legal certainty, and human rights protection. This study uses normative legal research methods (normative juridical) with an emphasis on analysis of positive legal norms, legal principles, and relevant doctrines. Data was obtained through literature review by examining regulations, legal literature, previous research results, and other supporting sources. The results of the study show that the phenomenon of No Viral No Justice emerged as a response to low public trust in the performance of law enforcement officials and the slow handling of cases. Social media functions as a means of social control that is able to encourage transparency, accountability, and acceleration of handling certain cases. But on the other hand, reliance on virality has the potential to lead to reactive, and populist law enforcement, as well as give birth to public judgments that ignore the principle of presumption of innocence. These findings confirm that the phenomenon of No Viral No Justice has a dual impact that can simultaneously strengthen and include the principle of Equality Before the Law in criminal practice.